Information Content and Value Relevance of Depreciation: A Cross-Industry Analysis - Kang, Sok-Hyon; Zhao, Yuping (The Accounting Review, 2010)
ABSTRACT: Funds from Operations (FFO) is the prevailing performance measure in the Real Estate Investment Trust (REIT) industry. However, prior studies are inconclusive about the superiority of FFO over GAAP net income. Because depreciation is the largest reconciling item between FFO and net income, we examine the information content and value relevance of depreciation for both the REIT and non-REIT industries and report the following findings. First, accumulated depreciation is value-relevant for the REIT industry, whereas accumulated depreciation has little value relevance for comparably capital-intensive non-REIT industries. Second, accounting depreciation deviates from economic depreciation to a greater extent for REITs than for non-REIT industries. Third, accumulated depreciation has predictive ability for future revenues for REIT firms, but not for non-REIT firms. Finally, only the REIT industry displays all of these properties. In sum, evidence supports the REIT industry's assertion that GAAP depreciation consistently exceeds economic depreciation and that book value of assets is systematically understated.